Longitudinal Population Dynamics of Staphylococcus aureus in the Nasopharynx During the First Year of Life - Abdulgader, Shima M.; Robberts, Lourens; Ramjith, Jordache; Nduru, Polite M.; Dube, Felix; Gardner-Lubbe, Sugnet; Zar, Heather J.; Nicol, Mark P. (Frontiers in Genetics, 2019)
Background:Staphylococcus aureus colonization is a risk factor for invasive disease. Few studies have used strain genotype data to study S. aureus acquisition and carriage patterns. We investigated S. aureus nasopharyngeal carriage in infants in an intensively sampled South African birth cohort. Methods: Nasopharyngeal swabs were collected at birth and fortnightly from 137 infants through their first year of life. S. aureus was characterized by spa-typing. The incidence of S. aureus acquisition, and median carriage duration for each genotype was determined. S. aureus carriage patterns were defined by combining the carrier index (proportion of samples testing positive for S. aureus) with genotype diversity measures. Persistent or prolonged carriage were defined by a carrier index ≥0.8 or ≥0.5, respectively. Risk factors for time to acquisition of S. aureus were determined. Results: Eighty eight percent (121/137) of infants acquired S. aureus at least once. The incidence of acquisition at the species and genotype level was 1.83 and 2.8 episodes per child-year, respectively. No children had persistent carriage (defined as carrier index of >0.8). At the species level 6% had prolonged carriage, while only 2% had prolonged carriage with the same genotype. Carrier index correlated with the absolute number of spa-CCs carried by each infant (r = 0.5; 95% CI 0.35–0.62). Time to first acquisition of S. aureus was shorter in children from households with ≥5 individuals (HR 1.06, 95% CI 1.07–1.43), with S. aureus carrier mothers (HR; 1.5, 95% CI 1.2–2.47), or with a positive tuberculin skin test during the first year of life (HR; 1.81, 95% CI 0.97–3.3). Conclusion: Using measures of genotype diversity, we showed that S. aureus NP carriage is highly dynamic in infants. Prolonged carriage with a single strain occurred rarely; persistent carriage was not observed. A correlation was observed between carrier index and genotype diversity.